ANALISIS METODE COACHING TERHADAP KESIAPAN MENGHADAPI UJIAN NASIONAL SISWA KELAS IX SMP N 02 PAGUYANGAN KECAMATAN PAGUYANGAN KABUPATEN BREBES: Array - Lestari, Dian; Aristiyo, Dedi Nur (Universitas Peradaban, 2019)
The student’s learning process becomes a benchmark for student’s learning process in the school. The success of learning mathematics of 9th grade at SMP N 02 Paguyangan, Paguyangan District, Brebes Regency wich is still low, need further review tthrough coaching methods. One of the most important things in learning is the goal, with the aim of the student’s learning process more directed. Each student has their own goals or targets in learning so that, the benchmark of the successful of learning goal of each student is different. Student’s learning process give an effect for the the successful of learning’s students. Therefore, this study aims to find out the description of the student’s prepare for national mathematics examinations at 9th grade of junior hight school students through coaching. Objects in this study were 9th grade of SMP N 02 Paguyangan wich amounted to 94 students. Data collection was carried out through interviews, and documentation. The results showed that students were able to go through coaching stages with the FIRA conversation model and student coaching summary, and they prepare to national mathematics examinations are significant growth.